The participatory index of women's empowerment: development and an application in Tunisia - Quinn, NN; Lombardini, S (Taylor & Francis, 2023)
In this paper we develop the Participatory Index of Women’s Empowerment, an innovative measurement tool that reflects its subjects’ own perceptions of empowerment. Participatory measurement is a response to the paradoxical potential for measurement of empowerment to disempower. A simple stated choice experiment allows participants to implicitly reveal the trade-offs that they make between different indicators of empowerment. This permits participatory determination of the relative weights for each indicator in a composite index, through estimation of a random utility model. We demonstrate the implementation of PIWE through a pilot application in the context of a quasi-experimental impact evaluation of an Oxfam project in Tunisia. Despite a relatively small sample size, we can reject the hypothesis that participants’ perceptions of empowerment are consistent with equal weights. We find that the project had a significant positive impact on participants’ empowerment and find suggestive evidence of impact on their perceptions of empowerment.